Text Insertion By Utilizing Masking-Filtering Algorithms As Part of Text Message Security - El Rezen Purba, Doni; Desinta Purba (Jurnal Info Sains : Informatika dan Sains, 2021)
For a secret message to be read and understood by a specific person only, a way is needed to hide the message, namely by steganography. Steganography is the concealment of secret messages in other media, such as images, audio, or video, so that the media inserted into the message looks as usual. Digital photos are one of the container media that are widely used for data hiding. However, when processing images such as compression, rotation, noise, and so on, confidential messages in the picture are prone to damage or loss. Then it takes the correct steganography method to hide secret messages into images to keep messages safe, not damaged even if the container image is manipulated, and the hidden message can be extracted again. on this thesis, applied masking method – filtering. Masking-filtering is included in the spatial domain. Message hiding is done by manipulating the luminance value of the image. Its use is applied to color or grayscale images. Masking serves as a tagging place on the picture that can be inserted message. Filtering passes a value to the marked section. the result is a stego image where the news is integrated with the container image, more robust to image processing when compared to methods that are also classified in the spatial domain, such as the least significant bit.